Empirical evaluation of interest barrier effects - Daniel Dreßler; Uwe Scheuering (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We analyze the impact of changes in thin capitalization rules on corporations' capital structure. Thin capitalization rules prevent firms from deducting excessive interest expenses from their tax base. As of 2008, Germany has severely changed its thin capitalization rule by targeting interest payments instead of debt to equity ratios. The new rule has primarily been introduced to prohibit tax avoidance by multinationals. For reasons of non-discrimination, the rule is, however, equally attributable on the national level and it is applicable to both internal and external financing. The theoretical and analytical literature has brought forward many arguments stating that the new interest barrier is harmful to firms, distorting their financing decisions. Four years after its introduction, the time has come to empirically evaluate the interest barrier. The DAFNE database serves as our source of reference. We differentiate by firm characteristics, by industry and by kind of debt. We find that the interest barrier drove firms to lower their debt to assets ratios and their net interest payments. Opposing its original intention, it was, however, also the national firms which adjusted their capital structure, and it was external rather than internal debt which was reduced. Thus, the interest barrier does indeed affect financing decisions, but predominantly not in the intended way and not of the intended firms. Insensitivity analyses we examine highly leveraged and low profitable firms, which are likely to be subject to the interest barrier. The results suggest a debt-reducing interest barrier effect for these companies as well.
More recent version: http://hdl.handle.net/10419/123720
Keywords: F23; H25; H32; 330; Capital Structure; Corporate Taxation; Interest Barrier; Empirical Analysis; Firm-Level Data